(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research paper discusses a model for the formation of the skills of a student's self-educational activity in a credit-modular system of learning organization predicts the course of the process, targets, performance indicators, the specifics of self-educational activity, which is natural, purposeful, manageable and progressive, has the property of continuity, stability; reflects the logic and sequence of implementation of the motivational results of the stages. Also, the main feature is the pedagogical conditions under which the credit-modular system of organization of education acts as a factor in the formation of the skills of the student's self-educational activity. Thus, the use of objective diagnostic methods as a didactic alternative to assessment in credits, focused on the rationing of content units, formed the skills of a student's self-educational activity, which develops forms of self-assessment and self-control of a student in self-educational activity.